2014
DOI: 10.4276/030802214x14151078348558
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Occupational Therapy Job Advertisement Trends for Occupational Therapy Education

Abstract: Introduction: The aim of this study was to consider trends in occupational therapy workplace demands in Queensland between December 2009 and November 2011, as demonstrated by advertised job requirements. These trends are considered in the context of both undergraduate curriculum design and continuing professional development. Method: A mixed-methods approach was used. The content of occupational therapy job advertisements from four job databases over a 2-year period were examined using quantitative and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Of these, just over half were employed in the first two months post completing the course and three quarters by four months. A Queensland study (Broome & Gillen, ) and a previous Sydney study (Franklin et al ., ) reported a decline in occupational therapy jobs advertised during the December to January period, followed by a gradual increase with a peak in June to July, suggesting the first four months would be possibly the most difficult to gain employment. In this study, the majority was employed during this difficult employment period (November – March).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, just over half were employed in the first two months post completing the course and three quarters by four months. A Queensland study (Broome & Gillen, ) and a previous Sydney study (Franklin et al ., ) reported a decline in occupational therapy jobs advertised during the December to January period, followed by a gradual increase with a peak in June to July, suggesting the first four months would be possibly the most difficult to gain employment. In this study, the majority was employed during this difficult employment period (November – March).…”
Section: Discussionmentioning
confidence: 99%
“…It appears to be a worthwhile alternative or adjunct to employer surveys, with the advantages of currency, accessibility and low cost. Researchers even argued that results from their research challenged professional competency sets and found current curriculum wanting, (France 2010;Messum et al, 2011;Broome & Gillen, 2014). One third of the studies recommended that findings be used to inform curriculum development.…”
Section: Discussionmentioning
confidence: 99%
“…Others undertook periodic analyses to understand skill changes and trends (Sodhi & Son, 2010;Cramer & Tenzek, 2013;) with the intention of keeping skill requirements up to date (Wise, Henninger, & Kennon, 2011) or determining what skill sets preserve employability in rapidly changing and often global fields (Kennan, Cecez-Kecmanovic, Willard, & Wilson, 2009). More recently studies have focused on identifying high-demand areas of practice within professions (Wise et al, 2011;Broome & Gillen, 2014). In Canada, Workopolis (2014) provided the most indemand skills by employers across all job types, and compared the contents of online job postings with the available skills of candidates on the market to identify skill gaps.…”
Section: Study Intentmentioning
confidence: 99%
See 2 more Smart Citations